The Right to Strike in an International Context The International Perspective - Hepple, Bob (Canadian Labour & Employment Law Journal, 2009)
In the first part of this paper, the author reviews the historical development of the right to strike in international instruments. In his view, that process was shaped during the Cold War by an artificial dis- tinction between socioeconomic rights and civil and political rights, resulting in a narrow interpretation of freedom of association. The author argues that while workers' rights have more recently been con- ceived of asfundamental human rights, an emphasis on social justice is equally necessary. In this context, the right to strike is critical to main- taining an equilibrium of power between labour and capital, and thus to protecting the dignity and human rights of workers. Turning to the chal- lenges posed by globalization, the author suggests that countries can gain a "comparative institutional advantage" by pursuing a program of rights-based regulation or "regulated flexibility." On this view, employ- ment rights - including the right to strike - are beneficial to economic development. The question, then, is whether constitutionalizing the right to strike is the best way to ensure Canada's comparative advantage. In considering this question, several issues arise, including whether consti- tutionalization would lead to excessive limitations on the right to strike; whether it would undermine the majoritarian character of our collective bargaining system; and whether the application of abstract constitu- tional principles by judges is a suitable way of settling labour disputes.